1993
DOI: 10.1159/000175955
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Factors Associated with Pain in Acute Myocardial Infarction

Abstract: In an unselected population of 921 consecutive patients with acute myocardial infarction admitted to one single hospital, regardless of age and whether they were admitted to the coronary care unit or not, we describe the course of pain during hospitalization. Patients with a history of angina pectoris, patients with a particularly long delay time, and patients not transported by ambulance had the longest duration of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The pronounced variability in estimated severity of pain in AM1 patients has also been demonstrated in previous studies (Herlitz et al, 1986;Karlson et al, 1993). Earlier studies have also suggested that some subgroups of patients such as those with smaller infarcts (Herlitz et al, 1984;Nielsen et al, 1990) and elderly patients (Bayer, 1988) have less severe pain.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…The pronounced variability in estimated severity of pain in AM1 patients has also been demonstrated in previous studies (Herlitz et al, 1986;Karlson et al, 1993). Earlier studies have also suggested that some subgroups of patients such as those with smaller infarcts (Herlitz et al, 1984;Nielsen et al, 1990) and elderly patients (Bayer, 1988) have less severe pain.…”
Section: Discussionsupporting
confidence: 68%
“…The evaluation of the intensity and duration of chest pain by analyses of morphine consumption is likely to give a fairly reliable estimate of the clinical pain course in hospital (Herlitz, 1990;Nielsen et al, 1990;Karlson et al, 1993). Such an estimate could of course be criticized, since it has been reported that some patients with severe chest pain do not ask for adequate pain relief (Bondestam et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations